2013
DOI: 10.1186/1742-2094-10-39
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid therapy in a patient with cerebral amyloid angiopathy-related inflammation

Abstract: We studied longitudinal changes of the levels of anti-amyloid β (anti-Aβ) antibody, amyloid β (Aβ) protein, and interleukin 8 (IL-8) in cerebrospinal fluid (CSF) of a patient with cerebral amyloid angiopathy-related inflammation (CAA-ri) in whom steroid treatment resulted in clinical improvement. The diagnosis of CAA-ri was established with brain biopsy. Levels of anti-Aβ 42 antibody, Aβ 40, Aβ 42 and IL-8 in CSF were measured in the CAA-ri patient at 23 time points in the 8-month clinical course. These CSF sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 16 publications
0
32
0
Order By: Relevance
“…However, considering the less invasive procedure compared to CSF, further investigations in a larger population will be of certain interest. Second, the temporal relationship between anti-Aβ autoantibody levels and clinical and radiological improvement of CAA-ri strongly supports they are a specific trait of the VE and MHs processes (ARIA-like events) ( 13 , 16 , 21 , 46 ). Third, like in AD-treated patients, the increased CSF level of Aβ40 and Aβ42, the decreased amyloid-PET uptake, and the higher amounts of anti-Aβ autoantibodies indicate a transient massive drainage of Aβ from the brain and vascular deposits to its soluble forms ( 18 , 20 , 31 , 47 ).…”
Section: Anti-aβ Antibodies As Biomarker For Ariamentioning
confidence: 80%
See 1 more Smart Citation
“…However, considering the less invasive procedure compared to CSF, further investigations in a larger population will be of certain interest. Second, the temporal relationship between anti-Aβ autoantibody levels and clinical and radiological improvement of CAA-ri strongly supports they are a specific trait of the VE and MHs processes (ARIA-like events) ( 13 , 16 , 21 , 46 ). Third, like in AD-treated patients, the increased CSF level of Aβ40 and Aβ42, the decreased amyloid-PET uptake, and the higher amounts of anti-Aβ autoantibodies indicate a transient massive drainage of Aβ from the brain and vascular deposits to its soluble forms ( 18 , 20 , 31 , 47 ).…”
Section: Anti-aβ Antibodies As Biomarker For Ariamentioning
confidence: 80%
“…First, like in immunotherapy, the acute phase of CAA-ri is characterized by a specific immune reaction mediated by an increased amount of autologous CSF antibodies against the perivascular deposited Aβ typical of CAA ( 13 , 16 , 21 , 44 46 ). Although observed in a single case study, autoantibodies have been found to be intrathecally produced and specifically increased only in CSF, while no changes has been found in the plasma, thus reflecting the immune/inflammatory mechanisms restricted to the brain ( 13 ).…”
Section: Anti-aβ Antibodies As Biomarker For Ariamentioning
confidence: 99%
“…The search (Figure 2) identified 186 abstracts, and a further 44 from reference lists, giving a total of 230. After inclusion and exclusion criteria were applied, 104 publications were included which described 213 distinct pathologically proven cases of CAARI/ABRA, 4,7…”
Section: Resultsmentioning
confidence: 99%
“…8,9 Also, anti-Aβ antibodies and factors, in relation to inflammation and tissue damage, could be implicated in the initiation and progression of CAA-ri. 10 More convenient biomarkers related to CAA-ri, however, are required to begin treatments as soon as possible.…”
mentioning
confidence: 99%